Physical activity and risks of breast and colorectal cancer: a Mendelian randomisation analysis - Nikos Papadimitriou; Niki Dimou; Konstantinos K. Tsilidis; Barbara Banbury; Richard M. Martin; Sarah J. Lewis; Nabila Kazmi; Timothy M. Robinson; Demetrius Albanes; Krasimira Aleksandrova; Sonja I. Berndt; D. Timothy Bishop; et al. (Nature Communications, 2020)
Physical activity has been linked to lower risks of colorectal and breast cancer. Here, the authors present a Mendelian randomisation analysis supporting a potentially causal relationship between higher physical activity levels and lower risks of breast cancer and colorectal cancer.